Advancing crop resilience through nucleic acid innovations: rhizosphere engineering for food security and climate adaptation - Saeed, Qudsia; Mustafa, Adnan; Ali, Shahzaib; Tobiloba, Lasisi Hammed; Rebi, Ansa; Baloch, Sadia Babar; Mumtaz, Muhammad Zahid; Naveed, Muhammad; Farooq, Muhammad; Lu, Xiankai (International journal of biological macromolecules, 2025)
Rhizosphere engineering has emerged as a transformative strategy to address the pressing challenges of climate change, food security, and environmental sustainability. By harnessing the dynamic interactions between plants and microbes, and environmental processes, this approach offers innovative solutions for enhancing crop production, protecting against pests and diseases, and remediating contaminated environments. This review explores how rhizosphere engineering, both plant-based and microbe-based, can be leveraged to enhance crop productivity, manage pests and diseases, and remediate contaminated environments under shifting climate conditions. We examine the effects of climate change drivers such as elevated CO2, increased N deposition, rising temperatures, and altered precipitation patterns, on plant-microbe interactions and rhizosphere processes. We show that climate change impacts key functions, including respiration, decomposition and stabilization of soil organic matter, nutrient cycling, greenhouse gas emissions, and microbial community dynamics. Despite these challenges, engineered rhizospheres can mitigate adverse effects of climate change by improving rhizodeposition, nitrogen fixation, root architecture modification, selective microbe recruitment, and pathogen control, while enhancing carbon allocation and stabilization in soil. However, the deployment of these technologies is not without challenges. Ecological risks, such as unintended gene transfer and disruption of native microbial communities, as well as socioeconomic barriers, must be carefully addressed to ensure safe and scalable implementation. We identify critical research gaps such as the limited understanding of multi-taxon cooperation and scalability in engineered rhizosphere systems, and how mechanistic understanding of designer plants and microbes can advance crop production, protection, and environmental remediation in agriculture and agroforestry under global changes.
Keywords: Global changes; zemědělské plodiny; Plant-microbe interactions; Crop productivity; Crops, Agricultural; Synthetic biology; Soil Microbiology; Food security; Climate Change; rhizosféra; Genome engineering; Rhizosphere engineering; půdní mikrobiologie; Food Security; klimatické změny; zajištění potravin; Rhizosphere